Konsep Pemikiran Pendidikan Islam Imam Al-Ghazali - Basori Basori; Ernita Wira Hastuti; Latifa Nurul Audi; Windri Gusnita (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
When Islamic philosophy is discussed, it is imagined that there are several figures who are called Muslim philosophers such as Al-Kindi, Ibn Sina, Al-Farabi, Ibn Rushd, Al-Ghazali, and so on. The presence of these figures is indeed unavoidable, because from them we can get to know Islamic philosophy, but also because in them the seeds of Islamic philosophy were developed. (Daulay & Dahlan, 2021) Sufism in Islam goes through various phases and conditions. In each phase and condition that it goes through, only some aspects are contained. Regarding the moral aspect, in the Qur'an there are many verses that encourage asceticism, patience, surrender to Allah, willingness, love, faith, simple living, and everything that is required of every Muslim as the perfection of faith. The Qur'an itself states that the Messenger of Allah is the best role model for those who want to perfect themselves with these virtues in their most noble form (alTaftazani, 2003, pp. 10-11). The thoughts of Sufi figures in the study of Sufism are very diverse in form and each Sufi has different characteristics even though the estuary is the same, namely towards al-Haq (Allah swt.). For example, Ibn Arabi with his concept of wahdat al-wujud, al-Halaj with the concept of hulul, Rabiah al-Adawiyah with the concept of mahabbah and many more.